Effect of Shading on Cotton Yield and Quality on Different Fruiting Branches. Issue 6 (1st November 2013) - Lv, Fengjuan; Liu, Jingran; Ma, Yina; Chen, Ji; Keyoumu·Abudurezikekey, Abudou; Wang, Youhua; Chen, Binglin; Meng, Yali; Zhou, Zhiguo
ABSTRACT: Reduced radiation from air pollutants has become a major challenge to cotton ( Gossypium hirsutum L.) production. Field experiments were conducted using two cotton cultivars at three shading levels during boll development in Nanjing (32°02′ N, 118°50′ E), China, to determine the effect of shading on cotton yield and quality. Lint yield, distributions of yield within the plant and that of biomass within bolls, and the quality of fiber and seed were analyzed. Shading reduced lint yield (decreased by 17–22% and 35–38% under shading conditions S1 and S2, respectively) through reducing boll number and boll weight, but increased proportion of lint yield on the bottom five fruiting branches (FB1–5 ) by 2.1 to 2.4% and 3.4 to 4.3% under S1 and S2, respectively. The proportion of fiber biomass in the boll decreased significantly, whereas proportion of seed biomass increased with enhanced shading. Fiber was the most sensitive boll component to shading, the biomass of which under shading condition (S1, S2) decreased by 5.9 to 6.9% and 8.8 to 11.9%, respectively. Shading increased oil content but decreased protein content of the seed on FB3 . Seed oil and protein contents on FB7 and FB12 responded opposite to those on FB3 . Simultaneously, shading was advantageous to fiber length and micronaire but disadvantageous to fiber strength. The greater the shading enhanced, the more the abovementioned measurements were affected. Shading due to air pollutants alters biomass distribution within bolls and lint yield distribution within the plant. Bolls on the bottom fruiting branches are more tolerant of shading.